Twenty-first century Latin American narrative and postmodern feminism - Ponce de León, Gina (Cambridge Scholars Publishing, 2014)
The authors of Twenty-First Century Latin American Narrative and Postmodern Feminism argue that, while the more traditional feminists of the 20th century did not recognize in their theoretical and literary work the diversity of women's experiences, current Latin American post-feminist and post-modern writers are proposing a transgressive new social order, resulting in a more significant cultural resistance to the society they represent. The authors included in this volume show that the ...